Eligibility for low-dose computerized tomography screening among asbestos-exposed individuals - Natalie R Fitzgerald; William M Flanagan; William K Evans; Anthony B Miller (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: The study aimed to incorporate an estimate of risk for asbestos exposure in the Canadian Cancer Risk Management Lung Cancer (CRMM-LC) microsimulation model. METHODS: In CRMM-LC, a 3-year probability of developing lung cancer can be derived from different risk profiles. An asbestos-exposed cohort was simulated and different scenarios of low-dose computerized tomography (LDCT) screening were simulated. RESULTS: As annual LDCT screening among non-asbestos-exposed individuals is less cost-effective than biennial screening, all the scenarios modeled for an asbestos-exposed cohort were biennial. For individuals with a two-fold risk of asbestos-induced lung cancer to be eligible for biennial LDCT screening, a smoking history of ≥15 pack-years would be necessary. For non-smokers with asbestos exposure resulting in a relative risk (RR) for lung cancer, it is not cost-effective to screen those with a RR of 5, but it is cost-effective to screen those with a RR of 10 (the heavily exposed). CONCLUSION: Asbestos-exposed individuals with an estimated two-fold or more risk of lung cancer from asbestos-exposure are eligible for LDCT screening at all ages from 55-74 years if they have a cigarette smoking history of ≥15 pack-years. Asbestos-exposed individuals who are lifelong non-smokers are eligible for LDCT screening at all ages from 55-74 years if they have accumulated a degree of asbestos exposure resulting in an estimated risk of lung cancer of ≥10.